1998
DOI: 10.1021/ac9805753
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hemoglobin Variants by MALDI-TOF MS Using a Polyurethane Membrane as the Sample Support

Abstract: A new method for the sampling and off-site analysis of hemoglobin variants by mass spectrometry is reported. This technique uses a nonporous polyurethane membrane as the collection device and transportation medium of a blood sample for analysis. The same membrane is then used as the MALDI-TOF MS sample support for mass spectrometric analysis. Minimal invasive sample collection is afforded by collecting less than 1 µL of blood using a common lancet device. MALDI-TOF MS is performed directly on the membrane, aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 40 publications
3
42
1
Order By: Relevance
“…For high-throughput proteomics, the use of ZipTip C18 microcolumns becomes rather expensive in addition to being tedious. Regardless of the method of desalting, the peptide samples need to be concentrated after the removal of salt, and a number of eVective methods of concentrating peptide samples have been devised; these include the use of supports made of TeXon [5], polyethylene [6], polypropylene [7], and polyurethane [8,9]. An inexpensive MALDI sample support made with TeXon was recently described by Yuan and Desiderio [8] who showed that consistently good peptide mass spectra of trypsin-digested proteins were obtained using such plates.…”
mentioning
confidence: 99%
“…For high-throughput proteomics, the use of ZipTip C18 microcolumns becomes rather expensive in addition to being tedious. Regardless of the method of desalting, the peptide samples need to be concentrated after the removal of salt, and a number of eVective methods of concentrating peptide samples have been devised; these include the use of supports made of TeXon [5], polyethylene [6], polypropylene [7], and polyurethane [8,9]. An inexpensive MALDI sample support made with TeXon was recently described by Yuan and Desiderio [8] who showed that consistently good peptide mass spectra of trypsin-digested proteins were obtained using such plates.…”
mentioning
confidence: 99%
“…On the other hand, MALDI-TOF MS gives single-charge peptide ions and has been used for identification of some singlemutation Hb variants (9,10 ). The present report shows that MALDI-TOF MS can be use to identify Hb variants.…”
Section: Clinical Chemistrymentioning
confidence: 99%
“…McComb et al (McComb et al, 1997(McComb et al, , 1998Perreault et al, 2001) employed polyurethane (PU) as a platform to desalt protein samples. That research was based on a study by Oleschuk & Chow (1996), who showed that neutral species adsorb more strongly to PU than do charged species.…”
Section: E Polyurethanementioning
confidence: 99%